Characterisation of transcriptional elements regulating virulence during Parastagonospora nodorum infection of wheat - John, Evan Johann (Curtin University, 2021)
Recent advances have facilitated the identification of important virulence factors produced by the what pathogen Parastagonospora nodorum. Among these are necrotrophic effectors, but little is known regarding how they are regulated. This thesis presents the characterisation of important regulatory elements underpinning the disease that includes transcription factors and necrotrophic effector gene promoters.